A framework for massively multiplayer online game content generation - Alves, Tiago (2016)
In this paper we present a framework for the generation of content for massively multiplayer online games (MMO). We study several MMO games in order to understand common properties and present an open framework that aims to ease the development of content for this type of games by reducing developer effort and storage requirements. A consequence is the reduction of game development cost and the increase of the number of devices where the game can be deployed.